The impact on motivation of CLIL-izing EMI in science education. A longitudinal case study in pre-service teacher training - Esther Nieto Moreno de Diezmas; Beatriz García Fernández; José Reyes Ruiz-Gallardo (OmniaScience, 2024)
The objective of this study was to identify the impact of implementing English as a medium of instruction (EMI) drawing upon Content and Language Integrated Learning (CLIL) methodology in science for pre-service teachers. Lecturers in modern languages and science education collaborated to design and implement the "CLIL-ization of EMI" intervention. The sample was made up of 105 students, 55 of whom were given instruction in English, and 50 in their mother tongue, Spanish. Two instruments for motivation in English and science were applied before the intervention, two weeks and one year afterwards. Additionally, an open-ended questionnaire was used with the experimental group to gain a more in-depth insight into student perception of EMI. Results showed that the short intervention did not impact motivation towards learning English, but it did effect that for science contents in the short and long term. The student stance on the experimental instruction of science in English was highly positive.